2022
DOI: 10.1186/s12888-022-03985-1
|View full text |Cite
|
Sign up to set email alerts
|

Hope and depression: the mediating role of social support and spiritual coping in advanced cancer patients

Abstract: Background Depression is the most common mental disorder in patients with advanced cancer, which may lead to poor prognosis and low survival rate. This study aims to explore the serial multiple mediating roles of social support and spiritual coping between hope and depression among patients with advanced cancer. Methods A cross-sectional study was conducted in China between May and August 2020. A total of 442 advanced cancer patients were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 41 publications
0
23
0
2
Order By: Relevance
“…The growth of low level of self-efficacy can make individuals better use of the social support around them and believe in their ability to regard demands as challenges rather than treats (Weber et al, 2013). Similarly, a study (Tao et al, 2022) found that hope protected individuals from depression by enhancing social support (including the SSA dimension). Another study (Zhao et al, 2018) showed that resiliency moderated the relationship between social support and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of low level of self-efficacy can make individuals better use of the social support around them and believe in their ability to regard demands as challenges rather than treats (Weber et al, 2013). Similarly, a study (Tao et al, 2022) found that hope protected individuals from depression by enhancing social support (including the SSA dimension). Another study (Zhao et al, 2018) showed that resiliency moderated the relationship between social support and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐six studies were quantitative designs and were conducted in mainland China ( n = 18), Taiwan ( n = 6), and the USA ( n = 2). Among them, five studies explored spiritual needs (Cheng et al, 2018; Deng et al, 2015; Du et al, 2022), spiritual state (Cheng et al, 2019), and spiritual nursing needs (Li et al, 2017); 11 studies examined the correlation between spiritual aspects and other variables (Chang et al, 2022; Cho & Lu, 2017; Feng et al, 2021; Guo et al, 2022; Kao et al, 2013; Li et al, 2012, 2022; Tao et al, 2022; Wang & Lin, 2016; Yang et al, 2021; Yeung et al, 2014); seven studies were conducted to translate spirituality‐related instruments originally developed in Western countries into Chinese for use with Chinese people with cancer (Astrow et al, 2012; Lin et al, 2015; Liu et al, 2016; Lo et al, 2016; Tang & Kao, 2017; Xie et al, 2019; Zhao et al, 2019); and three studies aimed to examine the effects of interventions on the spirituality of Chinese people with cancer (Chen et al, 2021; Sun et al, 2021; Xiao et al, 2022). One study with a mixed methods design was conducted in mainland China to explore the quality of life (including a spiritual dimension) of breast cancer survivors (Cheng et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…were added (Cheng et al, 2018;Du et al, 2022;Zhao et al, 2019), and the term was paraphrased as 'heaven or deities' (Tao et al, 2022).…”
Section: Indicators Used In Measuring Spiritualitymentioning
confidence: 99%
“…SSRS scores <33 mean low social support, between 33 and 45 indicates moderate social support, and >45 is high social support. The reliability and validity were confirmed to be good, with Cronbach’s α ranging from 0.825 to 0.896 in older adults ( 23 ).…”
Section: Methodsmentioning
confidence: 90%